2015
DOI: 10.1016/j.buildenv.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

A semi-centralized, valveless and demand controlled ventilation system in comparison to other concepts in field tests

Abstract: The idea of adapting the air supply rate to the actual demand in a building is not a new one. In commercial buildings it is already state-of-the-art to establish a demand controlled ventilation, where the level of air flow is based on sensors or time control. In residential buildings however, mechanical ventilation systems, whether centralized or decentralized, are in most cases operated in a constant modus, providing fresh air regardless if the fresh air is needed or not, even though the technology and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The main cause for the large difference between standardised and measured HRE, is likely to be due to unbalanced flows. In a study of both centralised and decentralised systems Merzkirch et al found that systems that are unbalanced can lead to decreased heat exchange efficiency [20]. Flows in the Rural location would appear to be more balanced.…”
Section: Resultsmentioning
confidence: 99%
“…The main cause for the large difference between standardised and measured HRE, is likely to be due to unbalanced flows. In a study of both centralised and decentralised systems Merzkirch et al found that systems that are unbalanced can lead to decreased heat exchange efficiency [20]. Flows in the Rural location would appear to be more balanced.…”
Section: Resultsmentioning
confidence: 99%
“…However, existing buildings may pose problems during their modernisations or if the building uses change. A partial solution for lack of space involves use of a decentralised system consisting of the local ventilation unit dedicated to a limited number of rooms [32,[34][35][36][37].…”
Section: Air Quality Standardsmentioning
confidence: 99%
“…Centralized demand-based systems with the combined control strategy of CO 2 , TVOC and humidity are often proposed and simulated in studies. Their energy efficiency and overall performance are good, but we still have limited measured case studies where the benefits of demand-based systems are demonstrated [26].…”
Section: Introductionmentioning
confidence: 99%